Osteoarthritis: From Molecular Pathways to Therapeutic Advances - Veronese, Nicola (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
In this book, we have reported the most recent discoveries and updates regarding molecular pathways in osteoarthritis. In particular, the advances regarding therapeutical options, from a molecular point of view, are largely discussed.